200 kV pulse modulator for power supply of VEPP-5 injection complex electron gun - Akimov, V.E.; Kazarezov, I.V.; Korepanov, A.A. (Вопросы атомной науки и техники, 2004)
This paper describes a new 200 kV pulse modulator for the VEPP-5 complex preinjector electron gun. The pulse
former is based on the solid state IGBT-switch and the new high turn ratio pulse transformer (PT). New design
allows to simplify the performance of charge device due to the decrease of primary voltage and decrease of power
consumption because of partial energy recuperation to the primary circuit. Описується нова версія 200 кB-го модулятора електронної гармати для інжекційного комплексу ВЕПП-5.
Формувач імпульсів виконаний на твердотільному IGBT ключі; для зниження напруги на ключі при
порівняно малому імпульсному струмі імпульсний трансформатор виконаний зі збільшеним числом витків
вторинної обмотки і великим коефіцієнтом трансформації. Описывается новая версия 200 кВ-го модулятора электронной пушки для инжекционного комплекса
ВЭПП-5. Формирователь импульсов выполнен на твердотельном IGBT ключе; для снижения напряжения на
ключе при сравнительно малом импульсном токе импульсный трансформатор выполнен с увеличенным числом витков вторичной обмотки и большим коэффициентом трансформации.